Hubungan Cara Pemberian Makanan Pendamping Air Susu Ibu dengan Kejadian Stunting - Susanti, Ni; Erawati, Ni; Mahayati, Ni (Indonesian Journal Publisher, 2025)
The quality and quantity of weaning food.plays an important role in preventing stunting. Weaning food.is introduced and given gradually according to the first age of administration in the right amount and frequency with a texture adapted to the child's ability to digest. The aim of this research was to determine the relationship between how to provide complementary foods with breast milk and the incidence of stunting in toddlers in Tianyar Tengah Village. This research uses a cross sectional study approach, sampling using proportional random sampling technique. Data were collected using a questionnaire and processed into univariate and bivariate analysis using the Fisher exact test. The research population was toddlers aged 24 to 59 months in Central Tianyar Village with a sample of 58 toddlers. The results showed that of the 58 respondents studied, 30 toddlers (51.7%) received an inappropriate way of giving weaning food., 46 toddlers (79.3%) did not experience stunting, and 12 toddlers (20.7%) received an inappropriate way of giving weaning food. weaning food is not suitable for stunting. At a significance level of 5%, the p value = 0.000, meaning the hypothesis is accepted. In other words, there is a significant relationship between the way Weaning food is given and the incidence of stunting among toddlers in Tianyar Tengah Village, Kubu II Community Health Center UPTD Working Area in 2024. Suggestions to increase education to mothers regarding the appropriate way to give Weaning food.